Emerging Systemic Therapies in Advanced Unresectable Biliary Tract Cancer: Review and Canadian Perspective - Vincent C. Tam; Ravi Ramjeesingh; Ronald Burkes; Eric M. Yoshida; Sarah Doucette; Howard J. Lim (Current Oncology, 2022)
Biliary tract cancer (BTC) is a group of rare and aggressive malignancies with a dismal prognosis. There is currently a significant lack in effective treatment options for BTC, with gemcitabine-cisplatin remaining the first-line standard of care treatment for over a decade. A wave of investigational therapies, including new chemotherapy combinations, immunotherapy, and biomarker-driven targeted therapy have demonstrated promising results in BTC, and there is hope for many of these therapies to be incorporated into the Canadian treatment landscape in the near future. This review discusses the emerging therapies under investigation for BTC and provides a perspective on how they may fit into Canadian practice, with a focus on the barriers to treatment access.